Tutela da paisagem urbana e função social da cidade - Maria Clara Oliveira Santos (2019)
This study draws a path between several fields of territorial and environmental knowledges in order to raise national concern for the protection of urban landscapes. Revisiting the discussions about environment, space, place, territory and landscape, the analysis also goes through a so-called national subjectivity to draw the lines of what would be the vision of the paradise inscribed in the Brazilian landscape and how that imaginary remains powerful in the symbolic construction of our relationship with nature and with urbe. It then promotes an effort to bring to the national field of analysis the classification made by Denis Cosgrove through dominant and sub-dominant landscapes, based on the distinction of social groups; then it maps the European use of landscape protection systems with an emphasis on the praxis promoted by the Italian legal system. In a second moment, the study presents the attempts to protect the urban landscape from models inscribed in municipal legislation, and performs a counterpoint with those offered by the heritage office enabling a patrimonial label of cultural landscape. The emblematic case of the city of Rio de Janeiro being declared as a mankind heritage cultural landscape help shed some light on problems that should be taken into consideration. Finally, the study proposes the adoption by the Brazilian order of mechanisms to protect the urban landscape, so as to promote the protection of places representative of the interaction between man and the environment in cities can represent an advance in the realization of the social function of the city . The paradigmatic reading of the City Statute, based on a new axiological axis based on the protection of urban landscapes, enables a normative framework capable of structuring the creation and modification of legal instruments that aim, democratically and effectively, to regulate the various aspects of urban dynamics, point of dignifying the marks and values registered in the space, strengthening not only the environmental functionality in the cities, so the municipalities in the development of management plans and more efficient management in the protection of the environmental and social values of the territory, but also of promoting an integrative understanding of territorial policies that establish in all governmental levels a democratic and efficient dialogue for the promotion of the social function of the city.